Effects of Bacillus subtilis and Leuconostoc mesenteroides on the Quality Characteristics of Potato Garaetteok - Hyeji Lim; Sujin Oh; Misook Kim (Journal of Food Quality)
To investigate the texture and cooking properties of garaetteok elaborated with potato flour, experimental products were elaborated replacing partially the rice flour, traditionally used, with nonfermented (NF) or fermented potato flour with Bacillus subtilis (BS) or Leuconostoc mesenteroides (LM) in percentages of 15% (NF15, BS15, and LM15) and 20% (NF20, BS20, and LM20). The control product (CON) was made using only rice flours. The pH of garaetteok was significantly lower in the BS and LM groups compared to CON and NF. Titratable acidity was the highest in BS20 and LM15. LM groups showed similar textural profiles to CON. The addition of potato flour to garaetteok increased the turbidity of soup (tteokguk), but the fermentation significantly lowered its turbidity. During storage for 24 h, garaetteok with fermented potato flour showed the inhibition of starch retrogradation. All scores of LM15 and LM20 were better than other potato garaetteoks and similar to those of CON with the exception of color acceptance. Consequently, garaetteok-added potato flour fermented with L. mesenteroides was the most preferable in terms of texture, cooking, and sensory characteristics.